CLINICAL PHARMACEUTICAL EDUCATION AND CLINICAL PHARMACIST COMPETENCIES (Uzbekistan Open Conference, 2025)
The article presents an overview of the development of clinical pharmaceutical education and clinical pharmacy in developed countries, and the main competencies of a clinical pharmacist as the main specialist in the rational use of drugs.